2019
DOI: 10.1016/j.joule.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Electrocaloric Cooling Materials and Devices for Zero-Global-Warming-Potential, High-Efficiency Refrigeration

Abstract: Electrocaloric cooling technologies, enabled by the discovery of the giant electrocaloric effect in dielectrics more than a decade ago, represents a zero-globalwarming-potential, environment-benign cooling alternative. Benefited from its nature as an electricity-driven capacitor, the electrocaloric working body renders the great advantages in the energy efficiency and the device integration. The decade-long efforts on advancing the technology revealed many promising material candidates with matured manufacturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
156
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(170 citation statements)
references
References 125 publications
0
156
0
1
Order By: Relevance
“…Electrocaloric effect refers to the electric filed ( E )‐induced isothermal entropy change (Δ S ) or adiabatic temperature change (Δ T ) in polar materials. Electrocaloric effect is reversible, and it can be applied for electrocaloric cooling technology, which is considered as an environment‐friendly cooling alternative with high‐energy efficiency and miniaturized integration to replace current vapor‐compression‐based refrigeration 138‐145 . Figure 9A displays electrocaloric refrigeration cycle based on adiabatic temperature change in ferroelectrics 146 .…”
Section: Electrocaloric Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrocaloric effect refers to the electric filed ( E )‐induced isothermal entropy change (Δ S ) or adiabatic temperature change (Δ T ) in polar materials. Electrocaloric effect is reversible, and it can be applied for electrocaloric cooling technology, which is considered as an environment‐friendly cooling alternative with high‐energy efficiency and miniaturized integration to replace current vapor‐compression‐based refrigeration 138‐145 . Figure 9A displays electrocaloric refrigeration cycle based on adiabatic temperature change in ferroelectrics 146 .…”
Section: Electrocaloric Effectmentioning
confidence: 99%
“…Copyright 2019, The Royal Society of Chemistry. H and I, Electric field dependence of Δ T near room temperature for BT‐, BNT‐, KNN‐ and Pb‐based ceramics 19,62,138‐146,148‐163 …”
Section: Electrocaloric Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, how to instantaneously and reversibly form good thermal contact between the EC material and the heat source and sink is also a critical challenge in achieving high heat flux. [ 13 ]…”
Section: Figurementioning
confidence: 99%
“…Several researchers have concluded that caloric (ferroic) refrigeration and heat‐pumping technologies, which are still in the research and development phase, are the most important option for the future . These solid‐state technologies variously utilize magnetocaloric, electrocaloric, and mechanocaloric effects. A material that exhibits more than one of these effects is described as a multicaloric (multiferroic) material with multicaloric effects .…”
Section: Introductionmentioning
confidence: 99%